Y el trovar abandonó a Johan Vasquiz… (Carte Romanze, 2020)
The Galician-Portuguese songbook of the Vatican Library is a unique testimony of a tenso between the troubadours Lourenço and Johan Vasquiz de Talaveira. The text presents multiple problems of reading and interpretation, which is why this contribution reviews (and discusses) the hypotheses of the scholars who have analyzed this composition and, from them and the conflicting lessons, presents some novel proposals hoping to help clarify dark spots.